A multisource feedback tool to assess ward round leadership skills of senior paediatric trainees: (1) Development of tool. Issue 1075 (4th May 2015) - Lakshminarayana, Indumathy; Wall, David; Bindal, Taruna; Goodyear, Helen M
ABSTRACT: Background: Leading a ward round is an essential skill for hospital consultants and senior trainees but is rarely assessed during training. Objectives: To investigate the key attributes for ward round leadership and to use these results to develop a multisource feedback (MSF) tool to assess the ward round leadership skills of senior specialist trainees. Methods: A panel of experts comprising four senior paediatric consultants and two nurse managers were interviewed from May to August 2009. From analysis of the interview transcripts, 10 key themes emerged. A structured questionnaire based on the key themes was designed and sent electronically to paediatric consultants, nurses and trainees at a large university hospital (June–October 2010). Results: 81 consultants, nurses and trainees responded to the survey. The internal consistency of this tool was high (Cronbach's α 0.95). Factor analysis showed that five factors accounted for 72% of variance. The five key areas for ward round leadership were communication skills, preparation and organisation, teaching and enthusiasm, team working and punctuality; communication was the most important key theme. A MSF tool for ward round leadership skills was developed with these areas as five domains. Conclusions: We believe that this tool will add to the current assessment tools available by providing feedback about ward round leadership skills.